Carbamylated Erythropoietin Decreased Proliferation and Neurogenesis in the Subventricular Zone, but Not the Dentate Gyrus, After Irradiation to the Developing Rat Brain - Osato, Kazuhiro; Sato, Yoshiaki; Osato, Akari; Sato, Machiko; Zhu, Changlian; Leist, Marcel; Kuhn, Hans G.; Blomgren, Klas (Frontiers in Neurology, 2018)
Cranial radiotherapy for pediatric brain tumors causes progressive, debilitating late effects, including cognitive decline. Erythropoietin (EPO) has been shown to be neuroprotective and to promote neuroregeneration. Carbamylated erythropoietin (CEPO) retains the protective properties of EPO but is not erythrogenic. To study the effects of CEPO on the developing brain exposed to radiotherapy, a single irradiation (IR) dose of 6 Gy was administered to the brains of postnatal day 9 (P9) rats, and CEPO (40 μg/kg s.c.) was injected on P8, P9, P11, P13, and P15. To examine proliferation, 5-Bromo-2-deoxyuridine (BrdU) was injected on P15, P16, and P17. CEPO administration did not affect BrdU incorporation in the granule cell layer (GCL) of the hippocampus or in the subventricular zone (SVZ) as quantified 7 days after the last BrdU injection, whereas IR decreased BrdU incorporation in the GCL and SVZ by 63% and 18%, respectively. CEPO did not affect BrdU incorporation in the GCL of irradiated brains, although it was reduced even further (to 31%) in the SVZ. To evaluate the effect of CEPO on neurogenesis, BrdU/doublecortin double-positive cells were quantified. CEPO did not affect neurogenesis in non-irradiated brains, whereas IR decreased neurogenesis by 58% in the dentate gyrus (DG) but did not affect it in the SVZ. In the DG, CEPO did not affect the rate of neurogenesis following IR, whereas in the SVZ, the rate decreased by 30% following IR compared with the rate in vehicle-treated rats. Neither CEPO nor IR changed the number of microglia. In summary, CEPO did not promote neurogenesis in non-irradiated or irradiated rat brains and even aggravated the decreased neurogenesis in the SVZ. This raises concerns regarding the use of EPO-related compounds following radiotherapy.